1806 Ky. Acts 122, An Act to Amend the Several Acts for the Better Regulation of the Town of Lexington, § 3. - (:unkn) unknown (General Publisher, 1806)
Be it further enacted, That said trustees are herby authorised [sic] to make such regulations as they may deem necessary and proper, relative to the keeping of gun-powder in the said town of Lexington, and if necessary may prohibit any inhabitants of said town, from keeping in the settled parts thereof, any quantity of gun powder which might in case of fire be dangerous
--
Keywords: GUN POWDER STORAGE